beta-Endorphin induces nonconvulsive limbic seizures. - Henriksen, S J (1978)
The endogenous opioid peptide, beta-endorphin, induces nonconvulsive limbic epileptiform activity when administered intraventricularly to rats. Epileptiform activity is elicited by beta-endorphin in doses that are devoid of analgesic or behavioral signs. Equimolar intraventricular doses of morphine or of the enkephalin analog [DAIa2,Met5]enkephalin-NH2 fail to elicit this limbic epileptiform activity. These observations, together with the recent immunohistochemical localization of beta-endorphin to midline limbic structures, suggest that beta-endorphin may have an important role in the regulation of limbic excitability.